Faktor Yang Berhubungan Dengan Kepatuhan Konsumsi Fe Pada Ibu Hamil Di Wilayah Kerja PUskesmas Kandai - Icha Tritanti; Febriana Muchtar; Fithria Fithria (KOLONI, 2023)
Anemia refers to deficiency of hemoglobin in the body. Pregnant women are particularly vulnerable to anemia, which can lead to preterm birth, increased susceptibility to infections, and maternal and fetal mortality. Anemia in pregnancy is primarily caused by iron deficiency which causes inadequate hemoglobin production. This condition can be prevented by regular iron supplementation of at least 90 tablets throughout pregnancy. The government has appointed Community Health Centers, Integrated Health Posts and Village Midwives to regularly distribute iron supplement as a national program. The prevalence of anemia remained high which could be attributed to the low adherence of pregnant women in taking iron supplement. This study was conducted to identify the factors that relate the compliance in consuming iron supplement among pregnant women in the working area of Kandai Community Health Center. In this cross-sectional study, total sampling technique was employed to select 96 pregnant women who sought antenatal care at the Health Center from January to April 2023 as the population and samples. This study revealed that knowledge (P value = 0.000), education (P value = 0.005), and family support (P value = 0.000) significantly related the compliance of pregnant women in taking iron supplement. Whereas, the role of health workers was not found significant to the compliance.  Keywords: Anemia, Pregnant women, Compliance, Iron tablet